Process optimization for the in vitro growth and maintenance of human epidermal keratinocytes - Thahsin, Naima (BRAC University, 2016)
A Dissertation Submitted in Partial Fulfillment of the Requirements’ for the Degree of Master of Science in Biotechnology.